Behaviours and educational effect on the improvement of self-care among the diabetics - Aljuhani, Faisal Ahmad; Aloqbi, Waleed Jamal; Alshakhs, Israa Aqeel; Ali, Hawra Baqer Al; Abbad, Bayan Emad Al; Qari, Abdulaziz Abdulbasit; Alburaidi, Omar Mohammed; Aldablan, Ahmed Saud; Alruwaili, Abeer Nahi; Alharbi, Faisal Fahad; Alghamdi, Ashwaq Ali (International Journal Of Community Medicine And Public Health, 2022)
Globally diabetes causes a huge burden due its significant morbidity and mortality. In year 2019 almost 4.2 million people died from diabetic complications. Self-care is essential in management of diabetes since lifestyle modifications can successfully help in preventing diabetes associated complications. People with diabetes should engage in self-care practices to manage their condition. Diabetes education is essential to improve self-care for patients with the disease. The purpose of this research is to review the available information behaviours and educational effect on the improvement of self-care among the diabetics. A key element of diabetic management is sufficient knowledge of the disease as more education can develop a sense of empowerment and improve quality of life of patients. Patients with diabetes have demands that extend beyond just maintaining optimal glucose control and include preventing complications, limiting their impairment, and receiving rehabilitation. Healthy diet, exercise, blood sugar monitoring, adherence to medicine, strong problem-solving abilities, healthy coping mechanisms, and risk-reduction behaviours are the seven fundamental self-care behaviours in people with diabetes that predict positive results. Patient self-care is a cornerstone of diabetes care and is thought to increase patients' effectiveness in managing their condition by increasing awareness of the disease and enhancing prevention. It is evident from the available literature that diabetes education promotes self-care which has positive impact on health outcome and helps in managing the metabolic markers. Self-care among patients can only be encouraged through proper education at all healthcare levels.